A comparative assessment of alternatives to the full-leg radiograph for determining knee joint alignment - Navali Amir M; Bahari Leila Azhar; Nazari Behrouz (BMC, 2012)
Abstract Background The purpose of this study was to assess the concurrent validity of alternative measures of frontal plane knee alignment, namely the radiographic anatomic axis and two clinical measures in patients complaining of knee malalignment as compared with the mechanical axis on full-length radiograph of lower limbs. Methods The knee-alignment angle was measured in 100 knees of 50 subjects with the chief complaint of frontal knee malalignment according to the following methods: lower-limb mechanical axis on radiograph, lower-limb anatomic axis on radiograph, distance between medial femoral condyles or medial malleoli using a calliper and lower-limb alignment using a goniometer. Data were analyzed using Pearson's correlation coefficient and simple linear regression. Results The anatomic axis best correlated with the mechanical axis (r = 0.93, P<0.001), followed closely by the intercondylar/intermalleolar distance measured by calliper (r = 0.89, P<0.001). Significant correlation was also found between the mechanical-axis angle and the lower limb axis measured by goniometer (r = 0.67, P<0.001). Conclusions The anatomic axis on radiograph, the calliper method and to a lesser extent the goniometer measurement appear to be valid alternatives to the mechanical axis on full-leg radiograph for determining frontal plane knee alignment. These alternative measures have the potential to provide useful information regarding knee alignment and may increase the assessment of this parameter by clinicians and researchers.